The Effect of Good Corporate Governance Mechanisms and Financial Distress on The Timeliness of Financial Report Submission - Karina Helida Feprizon; Tri Joko Prasetyo; Chara Pratami Tidespania Tubarad (PT. Altaf Publishing Corp, 2025)
This study aims to analyze the influence of financial distress, the proportion of independent commissioners, the existence of an audit committee, and the size of the board of directors on the timeliness of financial reporting in non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2024. Timeliness of financial reporting is an important benchmark for ensuring information transparency and corporate accountability to stakeholders. The method used was a quantitative approach with logistic regression analysis, as the dependent variable is binary. The sample was determined using a purposive sampling technique, resulting in a total of 564 observations. The results indicate that the existence of an audit committee and the size of the board of directors have a positive and significant influence on the timeliness of financial reporting. Conversely, the level of financial distress and the proportion of independent commissioners do not show a significant effect. These findings emphasize the importance of strengthening corporate governance mechanisms, particularly the effectiveness of the audit committee and the structure of the board of directors, in promoting reporting accuracy. However, the role of independent commissioners and the company's financial condition do not significantly contribute to the timeliness of reporting.